Measuring the spectral signature of polar bears from a drone to improve their detection from space. (September 2019) - Chabot, Dominique; Stapleton, Seth; Francis, Charles M.
Abstract: The increasing spatial resolution of earth observation satellites is creating new opportunities to survey wildlife. Satellites could be particularly valuable for surveying polar bears ( Ursus maritimus ) because of their remote circumpolar distribution and status of concern in the face of Arctic warming. However, the white coloration of bears does not contrast well with sea ice or snow in panchromatic imagery. We took advantage of the close-range observation capabilities of a drone to determine the spectral signature of polar bears as they would appear in multispectral satellite imagery, capturing low-altitude (≤100 m) multispectral images of bears in natural landscapes in Churchill, Manitoba, Canada. The bears' spectral curves were similar to those previously measured from pelts, with reflectance increasing with wavelength through the visible spectrum, although live bears had higher reflectance than pelts in the red-edge and near-infrared region. Bears had sufficiently consistent reflectance across the overhead surface of their body that ≥50% of pixels comprising each subject could be confidently matched to its core spectral signature, boding well for detection in coarser satellite imagery. Bears were clearly distinguishable from snow by their much lower reflectance in the blue and green region, but could potentially be confounded with large bright boulders. Currently available multispectral satellite imagery may still be too coarse (1.2 m/pixel) to reliably detect polar bears on sea ice, but resolution will likely continue to increase in future systems. Drones are a useful tool to resolve the spectral signature of wildlife species that could potentially be detected in satellite imagery.